Chlamydia trachomatis diversity and pathogenesis in young South African women, related to HPV prevalence and risk - Kanyoka, Pride (Department of Pathology, 2025)
Sexually transmitted infections (STIs) pose a significant threat to women's reproductive health and significantly increase the risk of acquiring human immunodeficiency virus (HIV). Chlamydia trachomatis (CT) and human papillomavirus (HPV) infections are particularly prevalent among younger demographics, with young women experiencing higher rates of infection compared to men. Due to these often being asymptomatic, both CT and HPV infections are challenging to detect in the general population, unless specifically tested for, leading to chronic, persistent infections. The aim of this dissertation was to investigate the impact of urogenital CT infection and bacterial genetic diversity on protective and pathogenic immune responses in the lower reproductive tract of South African adolescent girls and young women (AGYW), and risks associated with HPV co-infection. Using a multiplex quantitative PCR (qPCR) assay, CT bacterial loads and plasmid copy number were measured in CT-positive (CT+) cervicovaginal samples from AGYW (15-19 years) who participated in the uCHOOSE study, a randomized cross-over study investigating the effect of hormonal contraceptives on biomarkers of genital tract inflammation. Luminex multiplex assays were used to measure cytokines, including interleukin (IL)-1β, IL-6, IL-17A, interferon (IFN)-, tumour necrosis factor (TNF)-α, and IL-10, all of which have previously been linked to CT protection or pathogenesis. Cervical cytobrush T-cell activation and CCR5 expression were determined using a 8-colour flow cytometry panel (including CD3, CD4, CCR5, CD38, HLA-DR, and Ki67; CD19 and CD14 [dump channel]). Genotyping of the CT ompA gene and high resolution multilocus sequence typing (hr-MLST) were performed to understand CT genetic diversity. HPV typing was performed by Linear Array Genotyping, which measured 36 HPV types. Prevalence and persistence of CT infection was high in this cohort of AGYW, with 21.5% (28/130) being CT+ at baseline, 8.4% (9/107) at crossover and 15.2% (14/92) at exit having CT infections. Despite all CT infections being asymptomatic, the median CT bacterial loads for the cohort were 454 omcB copies/µl (interquartile range [IQR], 52-1,349), and all CT strains contained a median of 9 plasmids/bacteria (IQR, 7-13). CT MOMP type was inferred from ompA sequencing, with genovar E being the most common (accounting for 39.5%; 17/43 of infections), followed by genovar D (27.9%; 12/43 of infections). Using hr-MLST, a total of 27 CT sequence types (STs) were identified, including 18 novel STs. ST3 (8/44) and ST12 (6/44) were the most common ST found circulating. CT-infected AGYW had higher concentrations of IL-1β, IFN-, and IL-17A in cervicovaginal secretions than CT-negative (CT–) counterparts. TNF-α and IL-6 levels were particularly elevated in those with higher CT bacterial loads. No significant differences in cervical CD4+ T cell activation or CCR5 expression was evident between CT-infected and uninfected AGYW, although both markers were generally expressed at high frequencies. Although all CT infections were asymptomatic, CT infection in this cohort was associated with elevated inflammatory cytokines, suggesting that inflammatory biomarkers are a more sensitive measure of mucosal tissue inflammation than clinical symptoms. A significant difference in IFN- concentrations was noted between CT ompA genovars, using one-way ANOVA (P = 0.0079), with genovar F being lower. Similarly, CD4+CD38+ expression differed significantly by ompA genovar (p = 0.0438), with Ia being lower. Similarly to CT prevalence, AGYW had high prevalence of HPV overall, with 94.4% (102/108) being infected with any HPV at study baseline and 90.5% (86/95) being infected at crossover. HPV-35, HPV-52 and HPV 62/81 were the most common HPVs detected. About 80% of AGYW were infected with HR-HPV types, and over 80% had persistent infections lasting more than four months. Instances of multiple HPV types were more frequent than single infections. Every AGYW in this cohort infected with CT also had an HPV infection, and HPV infections, especially with high-risk HPV-16, was more prevalent in CT+ than CT– AGYW, as was rates of multiple HPV infections. The high prevalence and persistence of CT and HR HPV infections in these AGYW, both of which were asymptomatic despite being associated with evident inflammatory cytokine changes, may increase HIV acquisition and transmission risk. Data presented in this dissertation argues for an urgent need for policy change in South Africa away from World Health Organization (WHO) syndromic management of STIs, which lacks sensitivity and specificity. Furthermore, while AGYW are currently being vaccinated using Cervarix® vaccine for HPV-16 and HPV-18, the non-HPV-16/18 types commonly found in this cohort argue for the need for a broader vaccination strategy (eg. Gardasil®9). Public health initiatives are needed to be implemented to reduce the burden of clinically asymptomatic but inflammation causing infections with CT among young women by wider roll-out of near pointof-care (POC) or true POC STI screening tests.